The preservation of ancient DNA in archaeological fish bone - Ferrari, G; Cuevas, A; Gondek-Wyrozemska, AT; Ballantyne, R; Kersten, O; Pálsdóttir, AH; van der Jagt, I; Hufthammer, AK; Ystgaard, I; Wickler, S; Bigelow, GF; Harland, J; et al. (Elsevier BV, 2021)
The field of ancient DNA is dominated by studies focusing on terrestrial vertebrates. This taxonomic bias limits our understanding of endogenous DNA preservation for species with different bone physiology, such as teleost fish. Teleost bone is typically brittle, porous, lightweight, and is characterized by a lack of bone remodeling during growth. All of these factors potentially affect DNA preservation. Using high-throughput shotgun sequencing, we here investigate the preservation of DNA in a range of different bone elements from over 200 archaeological Atlantic cod (Gadus morhua) specimens from 38 sites in northern Europe, dating up to 8000 years before present. We observe that the majority of archaeological sites (79%) yield endogenous DNA, with 40% of sites providing samples containing high levels (>20%). Library preparation success and levels of endogenous DNA depend mainly on excavation site and pre-extraction laboratory treatment. The use of pre-extraction treatments lowers the rate of libraries that can be sequenced, although — if successful — the fraction of endogenous DNA can be improved by several orders of magnitude. This trade-off between library preparation success and levels of endogenous DNA allows for alternative extraction strategies depending on the requirements of down-stream analyses and research questions. Finally, we do not find particular bone elements to yield higher levels of endogenous DNA, as is the case for denser bones in mammals. Our results highlight the potential of archaeological fish bone as a source for ancient DNA and suggest a possible role of bone remodeling in the preservation of endogenous DNA. Leverhulme Trust Research Council of Norway